Enhanced Stability of Gr, h-BN and Gr/h-BN protected MoS2 flakes under laser illumination - Chak-Ming Liu; Sheng-Yu Hsu; Hsin-Sung Chen; Chuan-Che Hsu; Yann-Wen Lan; Hsiang-Chih Chiu; Wen-Chin Lin (Applied Surface Science Advances)
The optical excitation and applications of molybdenum disulfide (MoS₂) is critical due to its limited thickness and susceptibility to damage from high-intensity laser illumination, which can cause significant local heating and structural degradation. To mitigate this issue, protective layers made from materials with high thermal conductivity and transparency, such as graphene (Gr), hexagonal boron nitride (h-BN), and Gr/h-BN heterostructure, have been explored. This study utilizes Raman and photoluminescence (PL) spectroscopy to assess the stability of both bare MoS₂ flakes and MoS₂ flakes covered with different protecting layers under varying laser power levels. When exposed to 13 mW/μm2 laser for 30 min, bare MoS₂ undergoes considerable structural degradation, characterized by the formation of protrusions and a reduction in the Raman signal to just 10 % of its original intensity. In contrast, the Gr/MoS₂ heterostructure maintains the stability of both the Raman fingerprint peaks and PL intensity, with only a 0–15 % decrease. The h-BN/MoS₂ system also shows improved stability, with the Raman signal decreasing to around 30 % of its initial intensity. Gr/h-BN/MoS₂ exhibits similar stability to Gr/MoS₂. These findings indicate that the Gr/MoS₂ system provides the highest stability under laser illumination, followed by the Gr/h-BN/MoS₂ system and the h-BN/MoS₂ system, while bare MoS₂ demonstrates the lowest stability. The combined effects of efficient thermal dissipation and isolation from ambient oxygen offer significant protection to MoS₂ under high-power illumination.